Mobile and Wireless Technologies 2016 - Kim, Kuinam J.; Wattanapongsakorn, Naruemon; Joukov, Nikolai (Lecture Notes in Electrical Engineering, 2016)
This book presents the peer-reviewed contributions of ICMWT2016, an international conference devoted to mobile and wireless technology. Researchers and professionals from academia and industry met to discuss the cutting-edge developments in the field. The book includes papers on mobile and wireless networks, the increasingly important security issues, data management, as well as the latest developments in mobile software development.